THE PHENOMENON OF VIRTUAL IDENTITY: THE CONTEMPORARY CONDITION OF THE PROBLEM - E. L. Soldatova; D. N. Pogorelov (Образование и наука)
Introduction. Modern society is characterized by the formation of a new socio-cultural environment, which is based on a wide access to a variety of sources of information. Mass distribution of the Internet has a direct impact on socialization processes of the representatives of “Z-generation” who spend enormous amount of time in a cyberspace, quite often losing at the same time an ability of real personal development, interest in acquisition of skills for real interaction and effective communication. In this regard, the research of a phenomenon of a new, virtual identity of the personality, which is formed in the Internet environment, is brought into focus.The aim of the present publication is to consider the current level of knowledge in the field of virtual identity and systematization of scientific knowledge of this phenomenon.Methodology and research methods. Theoretical analysis, methods of synthesis and generalization were used.Results and scientific novelty. Various approaches to interpretation of virtual identity are considered; research tendencies are highlighted. The concepts “real identity” and “virtual identity” are viewed in relation to each other; the features and risks of virtual identity formation are revealed. The functions of virtual identity are specified. It is revealed that virtual identity reflects the subjectively significant image of the “Ideal-I” which is compiled from the completed material, character set and graphic images of the Internet environment, and therefore does not possess the uniqueness. Factors of designing by the person of virtual identity are described. Virtual identity can arise as a result of dissatisfaction with real identity, as a consequence of the identification crisis, in which the individual loses integrity. At the same time, it is shown that the cyberspace gives ample opportunities for self-expression and maximum personal fulfillment, realization of qualities, playing of roles and experience of emotions which turn out to be frustrated under any circumstances in real life.Problem areas of excessive immersion into virtual space are identified. An immature personality can lose life orientations as well as acquire the programmed decisions and ready cogitative patterns through excessive Internet use. The social activity in the Internet environment significantly reduces the moral level of communication on social networking sites and messengers. Aspiration always “to be online”, fear to miss a new message or a post aggravate anxiety of the user, increase the feeling of fatigue and uncontrollable temper, scant attention and strongwilled self-regulation, aggravation of a hypodynamia.The authors conclude that is required to continue to study the specifics of socialization in the Internet environment since it generates new forms of age development, changes the tasks and ideas of children and teenagers about social relations, and transforms an ideal image of the subsequent age stages in their consciousness.Practical significance. The results of the work carried out can be applied in the activities of teachers, social educators, educators, psychologists and other specialists who deal with the questions of socialization of modern children and adolescents.